Unsteady Flow Produced by Oscillations of Eccentric Rotating Disks - Ersoy, H. Volkan (HINDAWI LTD, 2012)
While the disks are initially rotating eccentrically, the unsteady flow caused by their oscillations in their own planes and in the opposite directions is studied. The analytical solutions to the problem are obtained for both small and large times, and thus the velocity field is determined for every value of time. The variations of all the parameters on the flow are scrutinized by means of the graphical representations. In particular, the effect of the ratio of the frequency of oscillation to the angular velocity of the disks is analyzed. The dependence of the oscillations in both x- and y-directions on the flow is examined. The influence of the Reynolds number is also investigated.
Keywords: NON-TORSIONAL OSCILLATIONS; NONCOAXIAL ROTATIONS; POROUS DISK; FLUID; AXES; Engineering; Mathematics